Physical violence, self rated health, and morbidity: is gender significant for victimisation?. Issue 1 (18th December 2003) - Sundaram, V; Helweg-Larsen, K; Laursen, B; Bjerregaard, P
Abstract : Study objective: To analyse gender differences in associations between physical violence and self rated health and self reported morbidity among a random sample of adults in Denmark. Design and setting: Two questions on self rated health and self reported morbidity respectively, were obtained from a cross sectional national health interview survey conducted among 12 028 adults (16 years +) in Denmark in 2000. A question on six different forms of physical violence was obtained from a supplementary self administered questionnaire given to the same sample. The reporting period for experienced physical violence was the past 12 months and for morbidity symptoms, the past 14 days. Main results: Men aged 16–24 years were significantly more likely to have experienced violence than women (OR = 3.2, 95% CI = 2.3 to 4.2). Female victims of physical violence were significantly more likely to rate their health as poor (OR = 2.02, 95% CI = 1.41 to 2.89) and to report anxiety (OR = 2.14, 95% CI = 1.35 to 3.37), depression (OR = 2.36, 95% CI = 1.55 to 3.60), and stomach ache (OR = 1.58, 95% CI = 1.01 to 2.47) than female non-victims. Male victims of physical violence were only significantly more likely to report stomach ache (OR = 1.73, 95% CI = 1.03 to 2.89) than male non-victims. Conclusions: Associations between physical violence and poor self rated health and self reported morbidity were found to be significant for women, but not for men. It is probable that gender differences in experiences of violence, as well as gender differences in health related self perception, contribute to a gender specific process of victimisation. Improved knowledge about the relation between gender specific violence and victimisation as a gender specific consequence is essential for targeting violence prevention.